A STUDY OF THE ORION NEBULA CLUSTER AND ITS SURROUNDINGS - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1952)
From star counts on 5 infrared sensitive plates taken with the Tonantzintla Schmidt camera in the region of the Orion Nebula, the existence of 4 clusterings probably related to each other forming a chain is clearly revealed. Three of these clusterings are
BOL OBS TONAN TACUB
Keywords: STUDY, ORION, NEBULA, CLUSTER, SURROUNDINGS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS